2019
DOI: 10.1093/jnci/djy230
|View full text |Cite
|
Sign up to set email alerts
|

Targeting IDH1-Mutated Malignancies with NRF2 Blockade

Abstract: Background Neomorphic IDH1 mutations disrupt the redox balance by promoting reactive oxygen species (ROS) production. However, the mechanism by which IDH1-mutant cells maintain ROS homeostasis remains elusive. It is also not known whether reprogrammed ROS homeostasis establishes targetable vulnerability in IDH1-mutated cancers. Methods We investigated ROS homeostasis in wild-type (GSC827, GSC923, GSC627, and GSC711) and IDH1-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
69
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 71 publications
(73 citation statements)
references
References 26 publications
2
69
0
Order By: Relevance
“…In the present study, the NRF2-derived de novo glutathione synthesis pathway was targeted as a therapeutic approach for PCPGs with SDHB deficiency. Brusatol has been repeatedly shown to be a potent inhibitor for NRF2 and antioxidant pathways [24,[36][37][38][39]. Several studies have indicated that brusatol alone exhibits mild cytotoxic effects and is frequently evaluated as a sensitization approach to support other cytotoxic therapies such as radiation therapy and cisplatin [24,40,41].…”
Section: Discussionmentioning
confidence: 99%
“…In the present study, the NRF2-derived de novo glutathione synthesis pathway was targeted as a therapeutic approach for PCPGs with SDHB deficiency. Brusatol has been repeatedly shown to be a potent inhibitor for NRF2 and antioxidant pathways [24,[36][37][38][39]. Several studies have indicated that brusatol alone exhibits mild cytotoxic effects and is frequently evaluated as a sensitization approach to support other cytotoxic therapies such as radiation therapy and cisplatin [24,40,41].…”
Section: Discussionmentioning
confidence: 99%
“…The same group also demonstrated that isocitrate dehydrogenase (IDH) 1-mutated glioma cells are dependent on Nrf-2 signaling cascade. The inhibition of Nrf-2 by BT increased oxidative damage to DNA with reduction in proliferation of IDH1-mutated cells [34] . They also reported that Nrf-2 can promote glutathione synthesis and thereby display protective function towards IDH1-mutated cells [35] .…”
Section: Introductionmentioning
confidence: 94%
“…The abrogation of Nrf2/GSH pathway by BT resulted in potent anticancer effect on IDH1-mutated preclinical cancer models [35] . In addition, the effect of BT on glutathione metabolism, ROS production, and chemoresistance in breast cancer has been reported in the literature [33] , [34] , [35] , [36] , [37] . Besides, Yang et al described the effect of BT on various types of cancer cells, Nrf-2-guided gene transcription, and glutathione de novo synthesis [37] .…”
Section: Introductionmentioning
confidence: 99%
“…While the inhibitors, AG-120 and AG-221 elicit partial responses or complete remission in AML patients, preclinical responses in solid tumors are less consistent and less robust. To enhance the antitumor effect of IDH mut inhibitors, particularly in low-grade gliomas, a few preclinical studies investigated synthetic lethal interactions of these inhibitors, with other reagents such as NAMPT inhibitors [48], Bcl-2 inhibitors [49], NRF2 inhibitors [50], PARP inhibitors [51], and tyrosine kinase inhibitors [52]. The combinatorial regimens have proven to be more effective.…”
Section: Discussionmentioning
confidence: 99%